PENGARUH WAKTU PENYIMPANAN SAMPEL URIN SELAMA 2 JAM DAN 4 JAM PADA SUHU 2-8OC TERHADAP HASIL PEMERIKSAAN KIMIA URIN - Kamil Kamil (ITKES Wiyata Husada Samarinda, 2017)
Background: Urinalysis is one of the effective methods of supporting examination and comprehensive. The urine examination late can cause the changing of the results of a urinalysis, so it can change the patient’s diagnosis and governance. Methods: The sampling technique that is used was quota sampling with many 50 samples of patients in health laboratory UPTD province of East Kalimantan. Examination is conducted at May 2016 in health laboratory UPTD province of East Kalimantan. Data were analyzed with statistical correlation coefficients (spearman) test. Results: Research results based on the correlation coefficient test statistics (Spearman rank) of chemical urine parameters that influence at a time when is delayed 2 hours and 4 hours of glucose, protein, pH, specific gravity, ketones, leukocytes and erythrocytes. While the urine chemical parameters have no affect on the time when is delayed 2 hours and 4 hours of bilirubin, urobilinogen, and nitrite. Conclusion: There is the influence of time of sample storage urine for 2 hours and 4 hours at a temperature of 2-8oC against the examination result of glucose, protein, pH, specific gravity, ketones, leukocytes, erythrocytes and have no effect against the examination results of bilirubin, urobilinogen, and nitrite.